Do entrepreneurs matter? - Sascha O. Becker; Hans K. Hvide (Institute for the Study of Labor (IZA), 2013)
In the large literature on firm performance, economists have given little attention to entrepreneurs. We use deaths of more than 500 entrepreneurs as a source of exogenous variation, and ask whether this variation can explain shifts in firm performance. Using longitudinal data, we find large and sustained effects of entrepreneurs at all levels of the performance distribution. Entrepreneurs strongly affect firm growth patterns of both very young firms and for firms that have begun to mature. We do not find significant differences between small and larger firms, family and non-family firms, nor between firms located in urban and rural areas, but we do find stronger effects for founders with high human capital. Overall, the results suggest that an often overlooked factor - individual entrepreneurs - plays a large role in affecting firm performance.
Keywords: D21; D24; J23; L11; L25; G39; 330; entrepreneurship; firm performance; human capital